The impact of wind, solar, and other factors on the decline in wholesale power prices in the United States. (1st February 2021) - Mills, Andrew; Wiser, Ryan; Millstein, Dev; Carvallo, Juan Pablo; Gorman, Will; Seel, Joachim; Jeong, Seongeun
Highlights: Annual average prices declined by $19–64/MWh between 2008 and 2017 in the United States. Estimate counterfactual prices by changing a factor at a time in fundamental model. Dominant driver of decline in average wholesale price is fall in natural gas prices. Total impact of wind and solar on average prices is below $3/MWh. Isolating the impact of individual factors is limited by non-linear interactions. Abstract: Across multiple organized wholesale power markets in the United States, annual average prices declined by $19–64/MWh between 2008 and 2017 while retirements of thermal power plants accelerated. Several prominent changes over the last decade are often discussed as contributors to this decline in prices. These include growth in wind and solar, a reduction in the price of natural gas, and weakened load growth. Here we construct a fundamental supply curve model for each of seven organized wholesale market regions and use counterfactual simulations to assess the degree to which wind and solar—among other factors—have influenced wholesale electricity prices. We find that growth in wind and solar since 2008 reduced average annual wholesale electricity prices by less than $3/MWh. In contrast the decline in natural gas prices reduced wholesale prices by $7–53/MWh, depending on the region. This suggests that recent thermal-plant retirements in the U.S. are primarily due to low natural gas prices, not growth in wind and solar. Fully isolating the impact of individual factors, however, is limited by non-linear interactions between factors.